PROBLEMATIKA PENERAPAN METODE DRILL DALAM PEMBELAJARAN PAI PADA ANAK TUNAGRAHITA DI SLB BAITUL FATTAHU KINALI PASAMAN BARAT - Willia Safitri; Fajriyani Arsya (CV. ADIBA AISHA AMIRA, 2024)
This research is in the background, because in SLB Baitul Fattahu Kinali West Pasaman in the application of the Drill method for children with disabilities there are several obstacles, namely, teachers still experience difficulties in applying the Drill Method because students are still lacking focus in learning PAI and still have difficulties in understanding and remembering learning so that it is a challenge for teachers to sort out the suitable method to be applied in the learning process. The purpose of this study is to find out the problems of applying the Drill method in learning PAI prayer material for children with disabilities at SLB Baitul Fattahu Kinali West Pasaman. The results of the study show that in the application of the Drill method in the PAI subject, the prayer material at SLB Baitul Fattahu Kinali West Pasaman uses three steps, namely implementation preparation activities, core activities, and closing activities. The problems faced by teachers in the application of the PAI learning drill method for prayer material are teachers which comes from several forms, namely factors from circumstances that come from within the student himself or commonly called internal factors such as their IQ level is indeed low or below average.